Indonesian Foreign Politics: Archipelagic State's Strategy Through Maritime Diplomacy to Realize the World's Maritime Axis - Aris Zainul Aziz; Evi Dwi Hastri; Fitri Annisa Putri; Kholili Kholili (Wiraraja University, 2024)
The Indonesian nation is a country that has an archipelagic area larger than the land area. In addition, the archipelago in Indonesia is used as a center for shipping carried out by other countries. Of course, this is very good because it can improve the economy of the Indonesian people. However, this can also become a problem if it is not prevented or addressed because of the many violations that occur in the Indonesian archipelago, such as illegal fishing, piracy, violation of sovereignty boundaries, and many other violations. In overcoming this, of course, there is a need for maritime diplomacy between the Indonesian government and other countries which also aims to achieve their national interests. In addition, President Joko Widodo said during a campaign in 2014 to promote making the Indonesian nation the world's maritime axis. Indonesia has also succeeded in carrying out maritime diplomacy since the Djuanda Declaration in 1957 which resulted in the concept of an archipelagic state and the birth of a new norm.